2021
DOI: 10.1111/cpr.13154
|View full text |Cite
|
Sign up to set email alerts
|

Cellular stress response to extremely low‐frequency electromagnetic fields (ELF‐EMF): An explanation for controversial effects of ELF‐EMF on apoptosis

Abstract: In modern world, electromagnetic fields (EMFs) have become an inseparable part of routine life. Numerous electric power-generating human-made devices are now producing EMFs which are overlaid on those of earth's magnetic field. EMFs are usually identified with a 50 or 60 Hz frequency and therefore are classified under the extremely low-frequency, non-ionizing span of electromagnetic spectrum. 1 Due to these physical characteristics, ELF-EMFs are not capable of breaking molecular bond or inducing thermal effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 213 publications
(275 reference statements)
0
12
0
Order By: Relevance
“…Many studies report that non-ionizing, non-thermal, extremely low-frequency EMF can modulate apoptosis. However, the results of other studies differ and there is an opinion that statistically significant changes in apoptosis are not observed 49 . However, they did not observe a statistically significant difference in the study by Martinelli et al, when exposed to EMF (915 MHz) on cardiac cells, their structural tissue integrity, and the expression of apoptotic genes 50 .…”
Section: Discussionmentioning
confidence: 85%
“…Many studies report that non-ionizing, non-thermal, extremely low-frequency EMF can modulate apoptosis. However, the results of other studies differ and there is an opinion that statistically significant changes in apoptosis are not observed 49 . However, they did not observe a statistically significant difference in the study by Martinelli et al, when exposed to EMF (915 MHz) on cardiac cells, their structural tissue integrity, and the expression of apoptotic genes 50 .…”
Section: Discussionmentioning
confidence: 85%
“…The diagram (Fig. 14 ) showed that how the ELF-EMF might activate downstream signaling pathways and cellular responses (e.g., apoptosis, autophagy 61 , morphology change, differentiation) through oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years the cellular responses mobilized by PEMF exposure have come into clearer focus and commonly impinge upon calcium signaling and mitochondrial respiration (ROS) to reach fruition [14,20,[48][49][50][51][52][53]. One calcium-permeable channel in particular, the Transient Receptor Potential Cation Channel Subfamily C Member 1, or TRPC1, has received attention [20,22,23,27,28,52,54,55].…”
Section: Muscle-targeted Pemf Therapy and Metabolic Stabilizationmentioning
confidence: 99%